Hierarchical organization and inequality in an economy with an implicit market for productive time - Bertrand Candelon; Arnaud Dupuy (Institute for the Study of Labor (IZA), 2010)
This paper proposes an equilibrium theory of the organization of work in an economy with an implicit market for productive time. In this economy, agents have limited productive time and can choose to produce in autarky, buy productive time from helpers to increase own production or, sell their productive time to a leader and thereby give up own production. This implicit market gives rise to the formation of teams, organized in hierarchies with one leader at the top and helpers below. We show that relative to autarky, hierarchical organization leads to higher within and between team payoffs/productivity inequality. We investigate this link empirically in the context of road cycling. We show that the rise in performance inequality in the peloton since the 1970s is merely due to a rise in within team performance inequality and consistent with a change in the hierarchical organization of teams and an increase in the helping intensity within team.
Keywords: D2; D3; L22; 330; hierarchical organization; productive time; helping time; inequality; professional cycling